Understanding Strategies for Resilient Livelihoods by Masvingo Urban’s Vulnerable Groups During the Covid-19 Pandemic in Zimbabwe - BERNARD CHAZOVACHII (African Journal of Governance and Development, 2020)
Despite the devastating impact that COVID- 19 has caused across the globe, the voices of resilient women, the youth, the elderly and people living with disabilities remain unheard. The study sought to examine the adequacy of the resilient mechanisms adopted by selected vulnerable members in Masvingo urban in facilitating self- reliance under COVID19 induced lockdown conditions. The paper is informed by the Resilience Theory and employs an exploratory research methodology. The case study was found to be the useful design for the study. Data collection was done through the interviews, focus group discussion and document analysis. Thematic content analysis was used to analyse the qualitative data. Findings revealed the chronic nature of the COVID-19 pandemic to the youth, elderly women living with disabilities and the orphaned and vulnerable children. The study recommends that for the women, children and youth, the elderly and people living with disabilities to avert adversities through sustainable resilient livelihoods, they need to employ mediating processes that do not lie in an individual or the social environment but the transactions between the two.